Silvical Characteristics of Aquilaria Agallocha Roxb. - Beniwal, B. S. (Indian Forester, 1989)
Aquilaria agallocha (Agar-wood) is a very valuable tree of North-eastern region of India and is distributed along foot-hills of evergreen and semi-evergreen forests. The tree flowers and fruits at an age of 7 to 9 years. The capsules ripen in second week of June and 1500 seed weigh to a kg. Seed germinates in 10 to 12 days and is viable for 30 days. Initial germination is 65% and it reduces to 5% after three weeks. Regular plantations are not raised due to uncertainty of agar-wood formation. Agar-wood formation is regarded as a pathological product. Many workers have studied agar formation since 1929 but could not work out a suitable technique for agar-wood formation. Agar tree is attacked by a defoliator (larvae of family Thyrididae) which can be controlled by spraying 0.1% Fenitrotbion or Thiodon.